Determination of Zearalenone and their metabolites in sheep urine by ELISA Method. - Teqja, S; Mavromati, J (Journal of the Hellenic Veterinary Medical Society, 2024)
The Fusarium metabolite mycotoxin zearalenone (ZEA) is of concern because of its lifelong estrogenic effects in animals. Zeranol as its metabolite was a widely used in animals as growth promoters to increase body weight. But, the use of zeranol as a growth promotion in animals that produce products for human consumption has been banned in the European Union (EU). As no data exist on the occurrence of zearalenone and zeranol in sheep urine in Albania we have analyzed samples of them by ELISA method. The method is based on a competitive enzyme immunoassay, ELISA for the quantitative analysis of zearalenone and its metabolites in urine. The overall recoveries of the analysis were in range of 80% -103%. Eighty nine (n=89) sheep urine samples were taken in the study during the last 2 years until now. Eighty (n= 80) samples were found to be compliant below the Screening Target Concentration (Cut-Off) value (0.404 - 0.839 ng/ml). Nine (n=9) samples were found to be suspect with the ELISA method above the Cut-Off value. After analyzing the suspect samples with the UPLC-MS/MS confirmatory method, two (n=2) sheep urine samples were noncompliant above decision limit for confirmation (CCα). In the first sample concentration found are 1 and 1.5 in the second sample 3 and 4.5 µg/kg for α-Zeralanol and β-Zeralanol respectively. The high levels of α-Zeralanol and β-Zeralanol concentrations found in urine indicate a contamination of animal feed with Zearalenone. This comes as a consequence of poor animal feed storage and leads to the accumulation of ZEA before harvest time or abuse has occurred. Further studies should be conducted to contribute to the knowledge disposition of zearalenone and zeranol in animals to give an accurate answer about possible contamination or illegal use.